2010
DOI: 10.1186/1471-2407-10-111
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of Human Papillomavirus (HPV) testing for cervicalcancer screening: trial design and preliminary results (HPV FOCAL Trial)

Abstract: BackgroundIn the HPV FOCAL trial, we will establish the efficacy of hr-HPV DNA testing as a stand-alone screening test followed by liquid based cytology (LBC) triage of hr-HPV-positive women compared to LBC followed by hr-HPV triage with ≥ CIN3 as the outcome.Methods/DesignHPV-FOCAL is a randomized, controlled, three-armed study over a four year period conducted in British Columbia. It will recruit 33,000 women aged 25-65 through the province's population based cervical cancer screening program. Control arm: L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 27 publications
2
67
0
1
Order By: Relevance
“…Several studies have investigated the clinical relevance of testing for HPV in cervical screening programs, in Europe [29][30][31][32][33][34] and North America. 35,36 These studies as well as our study have shown strikingly concordant results regarding the extremely high predictive values of HPV testing. Only some of these studies have performed HPV genotyping, however.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have investigated the clinical relevance of testing for HPV in cervical screening programs, in Europe [29][30][31][32][33][34] and North America. 35,36 These studies as well as our study have shown strikingly concordant results regarding the extremely high predictive values of HPV testing. Only some of these studies have performed HPV genotyping, however.…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, follow-up visits are important for women in the peri-menopausal period. A previous study demonstrated that with the polarization of cervical pre-cancerous lesions regarding the incidence age of cervical cancer, attention should be paid to women around the age of 30 years and those after the age of 50 years (35). Follow-up visits should be increased for HPV-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…That approach would also provide cytotechnicians with a smaller case load having a higher lesion prevalence (that is, a higher signal-to-noise ratio) and an overall more rewarding reviewing experience 17,18,26 . To evaluate that approach, a randomized controlled trial (the hpv focal trial) currently underway in British Columbia is comparing triage using hpv testing followed by lbc (Pap) with triage using lbc followed by hpv dna testing 27 . Results from focal, other similar comparative trials 28 , and demonstration projects (implementing hpv testing alone as the primary screening test) will be useful when the time comes once again to update screening guidelines.…”
Section: Hpv-based and Other Promising Screening Technologiesmentioning
confidence: 99%